Eficacia antihelmintica de las avermectinas (ivermectina y doramectina) en equinos - Intriago Loor, Ángel Abel (2019)
The objective was to evaluate the efficacy of avermectin on the control of Strongylus spp in horses. 48 mestizo horses were used, located in the Membrillo parish, Bolívar canton, organized in a completely random design with a factorial arrangement of treatments. Factor A corresponded to the type of avermectin (doramectin, ivermectin and control) and Factor B at the ages of the animals (3, 4, 5 and> 5 years), with four repetitions. The presence of adults and eggs of Strongylus spp expressed in number per gram of feces (PAIGH) was evaluated. Stool analyzes were performed at ESPAM MFL biochemistry laboratory through the flotation coproparasitic technique. Descriptive analysis of the variables, paired comparisons, analysis of variance and average tests were performed. All horses had infestations with adults of Strongylus spp., with an average of 15.08 IPGH. No significant differences were found in the evaluated variables (P> 0.05). The presence of eggs was only detected in 41.7% of the animals, with an average of 0.98 IPGH. The avermectins reduced adult parasites from 16 to less than 3 PAIGH. The presence of eggs in feces depended on anthelmintic treatment. It is concluded that avermectin in its two modes of application has a greater efficacy in animals older than four years, which allows the active principle to be considered as an alternative for the control of internal parasites.